2023
DOI: 10.1021/acsami.3c04948
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Multifunctional Zinc Ion Sustained-Release Biocoating on the Surface of Carbon Fiber Reinforced Polyetheretherketone with Enhanced Anti-inflammatory Activity, Angiogenesis, and Osteogenesis

Abstract: Current treatments of carbon fiber-reinforced polyetheretherketone (CFRPEEK) as orthopedic implants remain unsatisfactory due to the bioinert surface. The multifunctionalization of CFRPEEK, which endows it with regulating the immune inflammatory response, promoting angiogenesis, and accelerating osseointegration, is critical to the intricate bone healing process. Herein, a multifunctional zinc ion sustained-release biocoating, consisting of a carboxylated graphene oxide, zinc ion, and chitosan layer, covalentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…During the bone defect healing and bone tissue regeneration, angiogenesis and osteogenesis were tightly interrelated. And moderate zinc ion and SIM have been reported that could promote angiogenesis in bone regeneration [ 39 , 62 ]. Therefore, other than the osteogenic activity, angiogenic activity of CP@SIM coated Zn alloys were investigated by migration assay, tube formation assay and in vivo chicken embryo allantoic membrane (CAM) assay.…”
Section: Resultsmentioning
confidence: 99%
“…During the bone defect healing and bone tissue regeneration, angiogenesis and osteogenesis were tightly interrelated. And moderate zinc ion and SIM have been reported that could promote angiogenesis in bone regeneration [ 39 , 62 ]. Therefore, other than the osteogenic activity, angiogenic activity of CP@SIM coated Zn alloys were investigated by migration assay, tube formation assay and in vivo chicken embryo allantoic membrane (CAM) assay.…”
Section: Resultsmentioning
confidence: 99%
“…After the implantation, the surrounding tissues will release damage factors and activate the host immune response, followed by the formation of fiber encapsulation around the implants. 11,14 As shown in Fig. 8A, a fibrous layer has formed around all implants.…”
Section: In Vivo Immune-inflammatory Response Assaymentioning
confidence: 92%
“…8,9 Despite all these advantages, the bioinertness of CFRPEEK, which may lead to implantation failure, still remains to be solved. So far, some surface functionalization strategies have been proposed for bioactive CFRPEEK, such as UV grafting, [10][11][12] wet chemical methods, 13,14 and plasma immersion. 15 Through these methods, active ingredients with osteogenic potential are loaded onto the surface of CFRPEEK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CS can control the multi-stage release of Zn 2+ and match it with various steps of bone integration. A covalently grafted multifunctional sustained-release coating composed of carboxylated graphene oxide (GC), Zn 2+ , and CS on the surface of CFR-PEEK (CP/GC@Zn/CS) was achieved by Zhao et al (2023) , which completed the rapid release of Zn 2+ in the initial stage, sustained release of Zn 2+ in the middle stage, and slow release of Zn 2+ in the late stage. The coating played a role in immune regulation, angiogenesis, and osteogenesis in stages.…”
Section: Modification For Enhanced Biopropertiesmentioning
confidence: 99%